Pengaruh Toxic Leadership Terhadap Kinerja Karyawan Gen Z Yang Aktif Di Media Sosial Melalui Kepuasan Kerja Dan Motivasi Kerja - Devi Nuryanti; Daniel Ong Kim Kui (Journal of Innovation Research and Knowledge, 2026)
This study aims to analyze the effect of toxic leadership on the performance of Generation Z employees who are active on social media, with job satisfaction and work motivation as mediating variables. This study uses a quantitative approach with a 5-point Likert survey of 320 Gen Z employees through purposive sampling. The sample size was determined using power analysis (GPower), while the data was processed using PLS-SEM in SmartPLS 4.0, including outer/inner model evaluation, bootstrapping, and data collection through questionnaires distributed to respondents aged 18 to 28 years. Analysis results reveal a unique phenomenon in which toxic leadership is empirically positively correlated with motivation and job satisfaction, contrary to general theoretical assumptions. These results indicate that Generation Z tends to perceive work pressure as a challenge and demonstrates high resilience, enabling them to maintain or even improve performance under toxic leadership. However, these positive effects are contextual and the long-term impact on employee mental health and loyalty needs to be considered.